Use of inter-proton nuclear Overhauser effects to assign the nuclear magnetic resonance spectra of oligodeoxynucleotide and hybrid duplexes in aqueous solution. - Reid, D; Salisbury, SA; Brown, T; Williams, D; Vasseur, J; Rayner, B; Imbach, J (1983)
Inter-proton nuclear Overhauser enhancements (NOEs) have been used to assign the aromatic, anomeric and 2' resonances in the 1H nuclear magnetic resonance spectrum of the duplex formed between d(T-C-A-C-A-T) and d(A-T-G-T-G-A). The same techniques have been applied to assignments in the hybrid duplex formed by d(T-C-A-C-A-T) with r(A-U-G-U-G-A). Comparison of intra-residue with inter-residue NOEs yields structural information which suggests that the conformations of both duplexes are similar. The NOEs are consistent with inter-proton distances measured from models of B-form DNA. Circular dichroic results confirm these deductions.